Super-utilisateurs ou super-spécialistes ? Cartographie des catalyseurs de la transformation numérique en agence d’architecture - Aurélie de Boissieu (Les Cahiers de la Recherche Architecturale, Urbaine et Paysagère)
The ability to adapt is a major issue in the world we are currently living in. After more than forty years of the evolution of digital tools, however, architectural studios are still struggling to keep up. Perpetual change is a violence in the workplace that should not be underestimated. Detailed knowledge of these phenomena is crucial in order for architects and future architects to be actors and not victims of these digital transformations.Although the transformation of a practice is due to multiple factors, we suggest focusing on just one of them; that is, the internal organization and, more particularly, the human agents of digital transformation. In order to establish a cartography of the human agents of transformation in architectural studios, we thus question the catalytic roles that they play.The research is based on qualitative data from interviews and participant observation. Their analysis aims to give the best account of the diversity and specificity of the roles and arrangements of digital players, to address their mental representations as well as the gaps that may exist between the formal and informal organizations that are observable in practice.The article shows the tensions that exist between specialist and generalist roles, especially in the context of changing digital practices. From BIM manager to computational designer, we show the range of possibilities for these actors to register in the organization of the agency, their difficulties, and the non-negligible part of their respective roles in driving change. We also question what these roles tell us about the evolution of the architectural profession.